Penerapan Model Pembelajaran Conceptual Understanding Procedures (Cups) Dengan Teknik Probing Prompting untuk Meningkatkan Kemampuan Komunikasi - Purnami, Erni Sri; Khanafiyah, Siti; Khumaedi, Khumaedi (UPEJ Unnes Physics Education Journal, 2018)
Science learning demands the student?s skill in communicating their knowledge before appliying it in daily life. Communication is one of cultural and national character value. The aim of this research was determine the enhancement of students communication skills by the application of Conceptual Understanding Procedures (CUPs) learning model with probing prompting technique. The design of this research was one group pretest posttest design. The data of communication skills were obtained by observation method and the data of concept understanding were obtained by test method. Communication skills enhancement were calculated using the gain test. The result of this research showed that the application of CUPs learning model with probing prompting technique can increase students? communication skills. The gain score of students? communication skills was 0,454 which include in medium category. The gain score of concept understanding was 0,480 which include in medium category. It could be concluded that the application of CUPs learning model with probing prompting technique could improve students? communication skills.